The Effect of Service Quality and Price towards Repurchase Intention - Saadah, Imas; Inayah, Wulan Nur; Supriyadi, Didit; Nugraha, Sukma; Solihat, Asri (Entrepreneurship Faculty, Universitas Garut, 2024)
Repurchase interest is an activity that occurs between consumers and companies in buying and selling transactions which characterizes a company's success in marketing its products. If repurchase interest is low, there will be a decrease in sales performance. The purposes of the study were understanding the service quality and price on repurchase intention as a marketing phenomenon. The population of this study was Indonesian Society, at least Shinzui consumers who have used Shinzui products. The survey was sent online and face to face 678 randomly, there by individuals had the send probability of being selected from the population and the representing as sample. The data analysis technique in this quantitative study utilized statistical approach. The program used to analyze the data with the regression method was Statistical Product and Service Solution (SPSS) to meet the criteria for data analysis using regression, an interval scale was utilized. The tecnique of analyzing the data in this study was regression. The data obtained in this study is accurate and reliable at 95% degree. Based on the results of research on the analysis of repurchase intention influenced by service quality and price. It is hoped that this research will be useful, especially for stakeholders in conducting research aimed at developing their companies.